Concurrent systemic antibiotics at catheter insertion and intravascular catheter-related infection in the ICU: a post hoc analysis using individual data from five large RCTs. (September 2021) - Buetti, Niccolò; Souweine, Bertrand; Mermel, Leonard; Mimoz, Olivier; Ruckly, Stéphane; Loiodice, Ambre; Mongardon, Nicolas; Lucet, Jean-Christophe; Parienti, Jean-Jacques; Timsit, Jean-François
Abstract: Objectives: Data on the impact of systemic antibiotics at the time of catheter insertion are scarce. Therefore, we assessed the association between concurrent antibiotic administration at insertion and short-term catheter-related infections. Methods: We used individual data gathered from five large, randomized, controlled ICU trials. We analysed adult patients who required arterial, short-term central venous or dialysis catheter insertion in the ICU. The effect of antibiotics at insertion on major catheter-related infection (MCRI), catheter-related bloodstream infection (CRBSI) and colonization was estimated using multivariate marginal Cox and propensity score models. Results: We included 10 269 patients and 18 743 catheters from 36 ICUs. Antibiotic use was ongoing at the time of 11 361 catheter insertions (60.6%). After adjusting for well-known risk factors for intravascular catheter infection, we observed a similar risk for MCRI (HR 0.83, 95%CI 0.62–1.10, p 0.19) and CRBSI (HR 0.85, 95%CI 0.60–1.22, p 0.38) between the antibiotic and no-antibiotic groups. A confirmatory analysis using propensity score showed consistent results. No specific antibiotic subclasses reduced the risk of MCRI. Non-fermenting Gram-negative bacilli were more frequently observed in the antibiotic group. Conclusions: Ongoing antibiotic administration at the time of catheter insertion was not associated with a decrease risk of catheter-related infections and should not be carried out for preventing such infections. Our results bring new insights to antimicrobial stewardship in critically ill patients and may direct empirical antimicrobial therapy if an intravascular catheter infection is suspected.